THE EFFECT OF PRODUCT QUALITY ON CONSUMER BUYING INTEREST WITH CUSTOMER SATISFACTION AS A VARIABLE INTERVENING ON THE MARKET SHARE OF LONDON PUBLIC HEALTHY CARE PRODUCT - Malvina Marchese; Alexander (PT. Radja Intercontinental Publishing, 2022)
This study aims to find out how the influence of product quality on consumer buying interest with customer satisfaction as an intervening variable on the market share of london public healthy care product. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The data analysis method in this study uses simple linear regression analysis to obtain a comprehensive picture of the influence of product quality variables on consumer buying interest using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used.